Benefits of auditing and hospital accreditation for improving quality of care: A literature review (Research, Society and Development, 2025)
Objective: To identify in the literature the benefits of auditing and/or accreditation for improving the quality of care in the hospital setting. Methodology: This research consists of an integrative literature review, using secondary sources from online databases such as LILACS, BDENF, and PubMed. The Health Sciences Descriptors (DeCS) “Accreditation,” “Nursing Audit,” and “Quality Improvement,” as well as the Medical Subject Headings (MeSH) “Accreditation,” “Nursing Audit,” and “Quality Improvement,” were used and combined with the Boolean operator “AND.” Results: A total of 60 studies were found, of which 54 (90%) were excluded based on various criteria, leaving 6 articles for analysis. All evaluated articles scored above 7.0 on the CASP questionnaire, being classified as category “A.” Conclusions: Despite challenges in adherence by some professionals, the benefits of hospital auditing and accreditation for improving quality are evident. Both methods are effective for situational diagnostics, assessment of patient satisfaction, and identification of errors, promoting democratic decision-making and management strategies that enhance the quality of care.